Analysis of the ratio between the plasticity of clay and the expansion capacity by changes in humidity and temperature (2021)
. Clay is a cohesive material that varies in volume due to changes in humidity and temperature. Its behavior is studied with physical and geotechnical characterization of the material. The experimental analysis of the expansiveness of clays is related to plasticity, which depends on the expansive minerals it contains. The objective is to analyze the relationship between the plasticity index and the expansion capacity due to changes in humidity and temperature; various types of clay from San José de Cúcuta, Colombia, were studied. Liquid limit and plastic limit were analyzed with which the plasticity index was determined. The test tube free expansion and calcination were carried out at 1000 °C to determine the volumetric change due to humidity and temperature, respectively. The clays with plasticity index of 10% - 20% presented expansion by humidity of 5% - 10% and by calcination of 0% - 10%, which indicates low expansion; while the clay with plasticity index of 20% - 40% presented expansion by moisture of 20% - 50% and by calcination of 25% - 50%, which indicates moderately high expansion. The results show that there is a relationship between plasticity index and the expansion capacity due to changes in humidity and temperature.